Sodium‐glucose co‐transporter‐2 inhibitors as add‐on therapy to insulin for type 1 diabetes mellitus: Systematic review and meta‐analysis of randomized controlled trials. Issue 7 (25th March 2018) - Yamada, Tomohide; Shojima, Nobuhiro; Noma, Hisashi; Yamauchi, Toshimasa; Kadowaki, Takashi
Abstract : New treatments for type 1 diabetes are an unmet need. We investigated the efficacy and safety of adding sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors to insulin for type 1 diabetes by conducting a meta‐analysis of prospective randomized, placebo‐controlled trials. A search of electronic databases up to October 2017 identified 1361 studies, of which 14 were investigated ( N = 4591). Meta‐analysis showed that SGLT2 inhibitor therapy significantly reduced glycated haemoglobin (HbA1c) concentration by 0.4% (95% confidence interval [CI] 0.35, 0.46; P < .001, I 2 = 0%), fasting plasma glucose by 1.14 mmol/L (95% CI 0.8, 1.47), body weight by 2.68 kg (95% CI 2.0, 3.36), and systolic blood pressure by 3.37 mmHg (95% CI 1.46, 5.28). In addition, bolus insulin decreased by 3.6 units/day (95% CI 2.0, 5.3), and basal insulin decreased by 4.2 units/day (95% CI 2.2, 6.3). Continuous glucose monitoring showed a decrease in glucose excursions compared with placebo, with reduced variation of mean blood glucose, glucose standard deviation, and mean amplitude of glucose excursion. There was no significant increase in the rate of hypoglycaemia or severe hypoglycaemia; however, SGLT2 inhibitor therapy increased diabetic ketoacidosis (odds ratio [OR] 3.38) and genital tract infection (OR 3.44). Add‐on SGLT2 inhibitor therapy might be advantageous for type 1 diabetes, but its use should be considered carefully.